Early Reinfection with Human Metapneumovirus in an Infant - Ebihara, Takashi (American Society for Microbiology, 2004)
Human metapneumovirus (hMPV) is one of the major pathogens of respiratory illness. Reinfection with hMPV occurs frequently throughout life. We describe an infant who was infected with two different hMPV strains during a period of only 1 month.